Decoding the genomic tree of life - Simonson, Anne B. (National Academy of Sciences, 2005)
Genomes hold within them the record of the evolution of life on Earth. But genome fusions and horizontal gene transfer (HGT) seem to have obscured sufficiently the gene sequence record such that it is difficult to reconstruct the phylogenetic tree of life. HGT among prokaryotes is not random, however. Some genes (informational genes) are more difficult to transfer than others (operational genes). Furthermore, environmental, metabolic, and genetic differences among organisms restrict HGT, so that prokaryotes preferentially share genes with other prokaryotes having properties in common, including genome size, genome G+C composition, carbon utilization, oxygen utilization/sensitivity, and temperature optima, further complicating attempts to reconstruct the tree of life. A new method of phylogenetic reconstruction based on gene presence and absence, called conditioned reconstruction, has improved our prospects for reconstructing prokaryotic evolution. It is also able to detect past genome fusions, such as the fusion that appears to have created the first eukaryote. This genome fusion between a deep branching eubacterium, possibly an ancestor of the cyanobacterium and a proteobacterium, with an archaeal eocyte (crenarchaea), appears to be the result of an early symbiosis. Given new tools and new genes from relevant organisms, it should soon be possible to test current and future fusion theories for the origin of eukaryotes and to discover the general outlines of the prokaryotic tree of life.